Proinflammatory response of canine trophoblasts to Brucella canis infection. - Andrea G Fernández; M Soledad Hielpos; Mariana C Ferrero; Carlos A Fossati; Pablo C Baldi (PLoS ONE, 2017)
Brucella canis infection is an important cause of late-term abortion in pregnant bitches. The pathophysiological mechanisms leading to B. canis-induced abortion are unknown, but heavily infected trophoblasts are consistently observed. As trophoblasts responses to other pathogens contribute to placental inflammation leading to abortion, the aim of the present study was to characterize the cytokine response of canine trophoblasts to B. canis infection. To achieve this, trophoblasts isolated from term placenta of healthy female dogs were infected with B. canis, culture supernatants were harvested for cytokine determinations, and the load of intracellular viable B. canis was determined at different times post-infection. Additionally, cytokine responses were assessed in non-infected trophoblasts stimulated with conditioned media (CM) from B. canis-infected canine monocytes and neutrophils. Finally, cytokine response and bacteria replication were assessed in canine placental explants infected ex vivo. B. canis successfully infected and replicated in primary canine trophoblasts, eliciting an increase in IL-8 and RANTES (CCL5) secretion. Moreover, the stimulation of trophoblasts with CM from B. canis-infected monocytes and neutrophils induced a significant increase in IL-8, IL-6 and RANTES secretion. B. canis replication was confirmed in infected placental explants and the infection elicited an increased secretion of TNF-α, IL-8, IL-6 and RANTES. This study shows that canine trophoblasts produce proinflammatory cytokines in response to B. canis infection and/or to stimulation with factors produced by infected monocytes and neutrophils. These cytokines may contribute to placental inflammation leading to abortion in B. canis-infected pregnant bitches.